2010
DOI: 10.1002/ptr.2962
|View full text |Cite
|
Sign up to set email alerts
|

Chemomodulation of the antioxidative enzymes and peroxidative damage in the colon of 1,2‐dimethyl hydrazine‐induced rats by ellagicacid

Abstract: Prevention of cancer remains a primary need and new chemopreventive agents must be developed for this purpose. Toward this goal, a chemopreventive study was conducted to evaluate the potential effect of ellagic acid (EA) against 1,2-dimethylhydrazine (DMH-) induced colon carcinogenesis in experimental rats. Rats were administered with DMH (20mg/kg body weight) subcutaneous injection once a week for 15 weeks and were supplemented with EA (60 mg/kg body weight/day orally). In the present study, the efficacy of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…Cyclin D1 has been implicated in controlling the G1/S cell cycle transition and perhaps the most important checkpoint in the mammalian cell cycle, which is frequently overexpressed in human colon adenocarcinomas [38,39]. In our work, EA significantly decreased the levels of cyclin D1, might be attributed to its antioxidant property [40]. Thus, it can be concluded that EA attenuates proliferation of colon carcinoma HCT-15 cells by inhibiting PCNA and cyclin D1 as revealed by immunoblot, thereby showing its antiproliferative effect [16].…”
Section: Discussionmentioning
confidence: 52%
“…Cyclin D1 has been implicated in controlling the G1/S cell cycle transition and perhaps the most important checkpoint in the mammalian cell cycle, which is frequently overexpressed in human colon adenocarcinomas [38,39]. In our work, EA significantly decreased the levels of cyclin D1, might be attributed to its antioxidant property [40]. Thus, it can be concluded that EA attenuates proliferation of colon carcinoma HCT-15 cells by inhibiting PCNA and cyclin D1 as revealed by immunoblot, thereby showing its antiproliferative effect [16].…”
Section: Discussionmentioning
confidence: 52%
“…Group 3 rats received s.c. injection of 1,2-dimethylhydrazine (20 mg ⁄ kg body weight) once a week for 15 weeks and Group 4 rats were administered 1,2-dimethylhydrazine for the first 15 weeks followed by treatment with ellagic acid 60 mg ⁄ kg body weight, p.o. every day as reported earlier [16] for the remaining 15 weeks. After 30 weeks of experimental period, the rats were anaesthetized by diethyl ether and killed by cervical decapitation after an overnight fast.…”
Section: Methodsmentioning
confidence: 67%
“…We have reported that ellagic acid suppresses colon cancer in rats [16]; however, the precise mechanism by which ellagic acid mediates its action against colorectal cancer is not completely elucidated. Recent studies addressed its anti-inflammatory effect [25].…”
Section: Discussionmentioning
confidence: 99%
“…We observed the initial lesions of ACF and development of small adenoma in DMH control group, whereas only ACFs and polyps, but not adenomas, were noted in the rest of the groups. Also some studies showed that DMH administration had increased levels of TNF- α and IL-6 and decreased endogenous antioxidant enzyme levels [27]. …”
Section: Discussionmentioning
confidence: 99%